THE CONTRIBUTION OF TRADITIONAL GAMES IN ESTABLISHING SELF-CONTROL CHILDREN - Bernadeta Tri Anjarwati Kusuma Wardani; Gregorius Ari Nugrahanta (PEDAGOGIK : JURNAL PENDIDIKAN, 2021)
This research intended to develop a traditional game guidebook to improve self-control for children aged 9-12. This research method was R&D. Research conducted involved seven validators for expert judgment, seven teachers who were certified educators for needs analysis, and six children through subjects of a limited trial of the developed traditional game guidebook. The results indicated that; 1) development of this traditional game guidebook using ADDIE, 2) traditional game guidebook belonging to the "Very good" quality strata, with an average of 3.81 (scale 1-4) and consideration "No revision needed", and 3) implementation of this traditional game guidebook affected self-control. The significance test indicated t(5) = 16.81; p = 0.00 (p < 0.05) and r = 0.99 which belonged in the strata "Big effect" and equivalent to 98.26%. Thus, this traditional game guidebook could interpret 98.26% of changes in the self-control of children. The traditional game guidebook showed the effectiveness of the N-gain score of 80.39% which corresponds to the "High" strata.